Celebrity Endorsement, Quality, and Pricing Boost Noodle Sales in Indonesia: Dukungan Selebriti, Kualitas, dan Harga Dongkrak Penjualan Mie di Indonesia - Nur Hamidah Nizariyah; Herlinda Maya Kumala Sari (Academia Open, 2024)
This study examines the impact of brand ambassador, product quality, and price on consumer buying interest in Lemonilo noodles among Sidoarjo residents. Using a quantitative approach with 96 purposively sampled respondents, data was collected via Likert scale questionnaires and analyzed with SPSS 26. The findings reveal that all three factors significantly influence buying interest. Employing NCT Dream as a brand ambassador effectively attracts consumers, the product quality meets expectations, and the pricing is appropriate for the market. PT Lemonilo should maintain these strategies while exploring additional promotional activities to expand their market reach. Highlights: 1. Significant Impact: Brand ambassador, product quality, and price influence consumer buying interest.2. Effective Endorsement: NCT Dream attracts significant consumer interest for Lemonilo noodles.3. Strategic Pricing: Lemonilo's pricing aligns well with perceived product quality. Keywords: Brand ambassador, Product quality, Price, Consumer buying interest, Lemonilo noodles